Application of semi-finished products from wild raw materials to increase the nutritional value of baked products - F. A. Bischokova; L. Z. Borieva; I. B. Shogenova (Новые технологии)
The task of food products manufacturing enriched with substances that make up for the deficiency of certain substances remains very urgent. In order to prevent a large number of diseases, everyday products, in particular, baked goods are enriched. To improve the qualitative and quantitative composition of bakery products, it is necessary to introduce components that provide diet and preventive nutrition.  It is necessary to use products of plant raw materials processing, including vegetable additives, fruit and berry raw materials in the form of various semiuseful ingredients. Pectin, inulin, cellulose, complexes of soluble and insoluble fibers of beets, apples, citrus fruits, etc., as well as wild raw materials can be sources of dietary fibers for bread enrichment.  The aim of the research is to develop the technology and formulation of baked products using semi-finished products from wild raw materials – blackberries and potassium. The addition of cranberry and blackberry puree has had a positive effect on the physical, chemical, organoleptic quality indicators, the products have acquired a pleasant berry flavor, and aroma, a brighter color of the crust, increased nutritional value.